Kinerja Karyawan Dalam Industri Perhotelan: Tinjauan Work Life Balance Dan Etika Kerja Dengan Peran Kepuasan Kerja - Ni Putu Ayu Sintya Saraswati; Sapta Rini Widyawati; Ni Putu Riska Kumara Dewi (CV. ITTC INDONESIA, 2026)
The hospitality industry is highly dependent on the quality of human resources, and employee performance is crucial for maintaining competitiveness and the sustainability of hotel operations. This study aims to examine how work ethic and work-life balance impact employee performance at the Cross Paasha Bali Seminyak Hotel, with job satisfaction as the mediating variable. This study selected a quantitative methodology with a causal associative design. Using the census method as the sampling technique, the population in this study was 78 hotel employees. The SmartPLS 4.0 program was selected to analyze primary data, which was collected through a Likert-scale questionnaire. The Structural Equation Modeling–Partial Least Squares (SEM-PLS) method was also used. The study findings indicate that work-life balance and work ethic have a positive and significant effect on job satisfaction. Although job satisfaction does not affect employee performance, work ethic has a positive and significant effect on employee performance, but work-life balance does not significantly affect employee performance. Furthermore, there is no evidence that job satisfaction mediates the effect of work ethic or work-life balance on employee performance. These findings indicate that improving employee performance in the hospitality industry does not solely depend on work-life balance and employee job satisfaction, but is more influenced by the implementation of a strong work ethic and other operational factors that directly drive employee performance